Pengaruh Kepemimpinan Kepala Sekolah dan Peran Komite Sekolah terhadap Mutu Pembelajaran di SDN Kecamatan Mesuji Makmur - Puri Rahayu; Dessy Wardiah; Nila Kesumawati (Journal on Education, 2025)
This research aims to find out and describe: 1). To determine the influence of the principal's leadership on the quality of learning at SDN Mesuji Makmur District. 2). To determine the influence of the school committee on the quality of learning at SDN Mesuji Makmur District. 3). To determine the influence of the leadership of the school principal and school committee together on the quality of learning at SDN Mesuji Makmur District. The type of this research is quantitative. The sample in this research was conducted at 5 elementary schools in Mesuji Makmur sub-district with a total of 70 teachers. The techniques used in this research were questionnaires and documentation. Data analysis techniques use normality tests, linearity tests, multicollinearity tests, and hypothesis tests using simple regression tests, multiple regression tests using the SPSS version 26 application. The results of this study show that there is a significant influence on the principal's leadership variables and the role of the school committee together. -the same for the quality of learning at SDN Mesuji Makmur District.